Diffusion capacity abnormalities for carbon monoxide in patients with COVID-19 at 3-month follow-up - Qin, Wei (Eur Respir J, 2021)
OBJECTIVE: To evaluate pulmonary function and clinical symptoms in coronavirus disease 2019 (COVID-19) survivors within 3 months after hospital discharge, and to identify risk factors associated with impaired lung function. METHODS AND MATERIAL: COVID-19 patients were prospectively followed-up with pulmonary function tests and clinical characteristics for 3 months following discharge from a hospital in Wuhan, China between January and February 2020. RESULTS: 647 patients were included. 87 (13%) patients presented with weakness, 63 (10%) with palpitations and 56 (9%) with dyspnoea. The prevalence of each of the three symptoms were markedly higher in severe patients than nonsevere patients (19% versus 10% for weakness, p=0.003; 14% versus 7% for palpitations, p=0.007; 12% versus 7% for dyspnoea, p=0.014). Results of multivariable regression showed increased odds of ongoing symptoms among severe patients (OR 1.7, 95% CI 1.1–2.6; p=0.026) or patients with longer hospital stays (OR 1.03, 95% CI 1.00–1.05; p=0.041). Pulmonary function test results were available for 81 patients, including 41 nonsevere and 40 severe patients. In this subgroup, 44 (54%) patients manifested abnormal diffusing capacity of the lung for carbon monoxide (D(LCO)) (68% severe versus 42% nonsevere patients, p=0.019). Chest computed tomography (CT) total severity score >10.5 (OR 10.4, 95% CI 2.5–44.1; p=0.001) on admission and acute respiratory distress syndrome (ARDS) (OR 4.6, 95% CI 1.4–15.5; p=0.014) were significantly associated with impaired D(LCO). Pulmonary interstitial damage may be associated with abnormal D(LCO). CONCLUSION: Pulmonary function, particularly D(LCO), declined in COVID-19 survivors. This decrease was associated with total severity score of chest CT >10.5 and ARDS occurrence. Pulmonary interstitial damage might contribute to the imparied D(LCO).